1990
DOI: 10.1007/bf02253713
|View full text |Cite
|
Sign up to set email alerts
|

Utility of an elevated plus-maze for the evaluation of memory in mice: effects of nootropics, scopolamine and electroconvulsive shock

Abstract: An elevated plus-maze consisting of two open and two enclosed arms was employed for an evaluation of memory in mice. Mice in the plus-maze escaped from the open arm to the enclosed arm because mice apparently dislike open and high spaces. The time it took for the mice to move from the open arm to the enclosed arm (transfer latency) was recorded. The transfer latency after the 2nd day was significantly shorter than that on the 1st day when it was recorded at a rate of one trial a day for 5 days. The transfer la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
174
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(177 citation statements)
references
References 37 publications
2
174
1
Order By: Relevance
“…The elevated plus-maze was used to evaluate spatial long-term memory, involving the previously described procedure (Itoh et al 1990(Itoh et al , 1991Maurice et al 1994). The apparatus consisted of two open arms (23.5 ϫ 8 cm), painted white, and two enclosed arms (23.5 ϫ 8 ϫ 20 cm high), painted black.…”
Section: Elevated Plus Maze Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The elevated plus-maze was used to evaluate spatial long-term memory, involving the previously described procedure (Itoh et al 1990(Itoh et al , 1991Maurice et al 1994). The apparatus consisted of two open arms (23.5 ϫ 8 cm), painted white, and two enclosed arms (23.5 ϫ 8 ϫ 20 cm high), painted black.…”
Section: Elevated Plus Maze Proceduresmentioning
confidence: 99%
“…The elevated plus-maze involving a protocol allowing a reliable measure of memory was used, with the benefit that similar instinctive cues as place preference conditioning were involved (Itoh et al 1990(Itoh et al , 1991. On day 1, animals were trained to learn the maze.…”
Section: Effects Of Selective Sigma 1 Receptor Antagonists On the Acqmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effects of 2-PMPA on acquisition and/or retrieval of memory, we used the elevated plus maze model of spatial learning in mice (Itoh et al, 1991). This paradigm is sensitive to the amnesic effects of post-training administration of scopolamine or electroconvulsive shock (Itoh et al, 1990), pretraining effects of scopolamine, MK-801 and diazepam (Itoh et al, 1991), and pretest effects of MK-801 and scopolamine (Hlinak and Krejci, 2000). Results of Experiment 5 demonstrating amnesic effects of MK-801 confirm earlier observations (Itoh et al, 1991); however, we found that in contrast to MK-801, 2-PMPA (50 and 100 mg/kg) affected neither learning nor retrieval of memory.…”
Section: Effects Of Gcp II Inhibition On Morphine-induced Conditionedmentioning
confidence: 99%
“…The elevated plus maze was used to evaluate short-term spatial memory [36]. Briefly, the elevated plus maze for mice consists of two perpendicular open arms (21.5 × 7.5 cm) and two closed arms (21.5 × 7.5 × 20 cm) which extends from a central 7.5 × 7.5 cm platform.…”
Section: Elevated Plusmentioning
confidence: 99%